2012
DOI: 10.1103/physrevlett.108.197203
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Induced Ferromagnetic Resonance in Magnetic Tunnel Junctions

Abstract: We demonstrate excitation of ferromagnetic resonance in CoFeB/MgO/CoFeB magnetic tunnel junctions (MTJs) by the combined action of voltage-controlled magnetic anisotropy (VCMA) and spin transfer torque (ST). Our measurements reveal that GHz-frequency VCMA torque and ST in low-resistance MTJs have similar magnitudes, and thus that both torques are equally important for understanding high-frequency voltage-driven magnetization dynamics in MTJs. As an example, we show that VCMA can increase the sensitivity of an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
190
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(211 citation statements)
references
References 36 publications
16
190
3
2
Order By: Relevance
“…Optimization of MTJ performance for these applications requires quantitative evaluation of the spin torque (ST) vector [12], magnetic damping [13], voltagecontrolled magnetic anisotropy [14][15][16], and the spectrum of magnetic excitations of the MTJ [17,18]. A common techniques for quantitative measurements of these properties is ST ferromagnetic resonance (ST-FMR) [19,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of MTJ performance for these applications requires quantitative evaluation of the spin torque (ST) vector [12], magnetic damping [13], voltagecontrolled magnetic anisotropy [14][15][16], and the spectrum of magnetic excitations of the MTJ [17,18]. A common techniques for quantitative measurements of these properties is ST ferromagnetic resonance (ST-FMR) [19,20].…”
mentioning
confidence: 99%
“…The amplitudes of the Lorentzians, V s and V a , are functions of the ST vector, magnetic parameters of the system [24], and voltage controlled magnetic anisotropy [16]. When the modulation field is small compared to the resonance linewidth in the field domain, the RMS voltage signalṼ mix (f ) measured by the lock-in amplifier is proportional to the first derivative of the rectified voltage V mix (f ) with respect to the modulated variable-the external magnetic field B:…”
mentioning
confidence: 99%
“…This phenomenon, called the spin-torque diode effect, can be used as an RF-detector of very high sensitivity [7]. Recently, it has been shown that similar behavior can be achieved with alternatingvoltage-controlled magnetic anisotropy (VCMA) [8,9]. In this paper we propose a voltage tunable spin-torque diode, that is capable of sensing RF signals of different frequencies.…”
mentioning
confidence: 99%
“…In this case, the dependence of the detected DC voltage on the angle between the microwave magnetic field h(t), causing the effect, and the bias magnetic field H, magnetizing the magnetic metal, is qualitatively different from the angular dependence of the rectification voltage caused by the anisotropic magnetoresitance [2,14,16,17]. Moreover, the discovered PHE based rectification process produces DC voltage even in the case when the detected magnetization dynamics is associated with short-wavelength spatially non-uniform spin waves parametrically excited in the magnetic metal.…”
mentioning
confidence: 98%